THE ROLE OF TECHNOLOGY IN NURSING DOCUMENTATION: A CHRONOLOGICAL REVIEW - Kiprawi, Mohd Safri (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2026)
This temporal literature review of The Role of Technology in Nursing Documentation aims to synthesise the trends and evolution of the digital integration in health. Although the use of technology, such as electronic health records, has been embraced, inconsistencies in their use, effectiveness, and fit with nursing processes suggest a need for a temporal perspective. To address this challenge, a thorough and sophisticated search was conducted in the Scopus database using keywords Electronic Health Records, Nursing Documentation, Digital Records, and Technology. A total of 114 primary studies were identified after reviewing the literature. The outcomes were clustered into four time periods to represent the trends in research activity and emphasis: (1) the Nascent and Exploratory Phase (2004-2008) that showed initial adoption and feasibility of the system; (2) the Initial Growth and Conceptual Expansion phase (2009-2013) that showed increasing interest and theoretical framework development; (3) the Consolidation and Fluctuating Maturity phase (2014-2022) that showed a steady state in publication output with variable effectiveness of the system and user adaptation; and (4) the Renewed Acceleration and Digital Transformation Phase (2024-2026) that showed an increase in innovation through digital transformation and integration of new technologies. The descriptive analysis of the temporal distribution of the studies shows an increasing trend in research activity, with the highest percentage in the recent phase. Overall, the review shows a dynamic trend in technology integration in nursing documentation with improvements and setbacks. The research concludes that although digital systems have greatly improved documentation, further development, user-friendly design, and policy support are needed to ensure they are being used to their full potential.